War in Iraq : planning and execution - Mahnken, Thomas G., 1965-; Keaney, Thomas A. (Cass series--strategy and history ;, 2007)
This volume provides a collection of insightful essays on all phases of the Iraq War: both US-led major combat operations to defeat the Ba'athist regime as well as efforts to reconstruct the country and defeat the insurgency. Written by leading scholars on the Iraq War, many of whom have practical first-hand experience of the war, the book includes a Conclusion by leading US strategic thinker Eliot Cohen. This is the first work on the Iraq War to incorporate an understanding of the Iraqi side of the war, based on a systematic analysis of captured Iraqi archives. War in Ira.